Design of a Rainwater Based Gravity Filtration System as a Sustainable Clean Water Solution for Household Scale in Kaliandra: Perancangan Sistem Filtrasi Gravitasi Berbasis Air Hujan sebagai Solusi Air Bersih Berkelanjutan Skala Rumah Tangga di Kaliandra - Izza Sadry Zulfandy; Moyo Anggoro Laksono (ANDIL Mulawarman Journal of Community Engagement, 2026)
The availability of clean water is still a challenge in various regions, especially in areas with limited water supply infrastructure. Indonesia has the potential for abundant rainfall as an alternative water source, but its use requires simple processing to meet water quality standards. This community service activity aims to design and implement a rainwaterbased gravity filtration system as a solution for providing sustainable clean water on a household scale. The method used is a design and build approach, including designing the structure of the device, determining the composition of the natural filtration media, as well as testing the performance of the system without the use of electrical energy and chemicals. The novelty of this activity lies in the development of appropriate technology that is simple, economical, environmentally friendly and easy to replicate by the community. The filtration system is designed using filter cotton media, fine sand, zeolite, activated carbon and gravel arranged in layers to remove suspended particles and improve the physical characteristics of rainwater. The design results show that the system has a simple design, is easy to assemble, and has the potential to improve water quality and community access to clean water. It is hoped that the implementation of this technology can support optimal use of rainwater, increase community independence, and contribute to achieving Sustainable Development Goals (SDGs) Goal 6 concerning safe and sustainable access to clean water.